+0  
 
+5
939
4
avatar+9 
how do I solve 42=-2(m+6)+6
darkanjel76  Jan 29, 2012
 #1
avatar+3077 
0
[input]42=-2(m+6)+6[/input]
admin  Jan 29, 2012
 #2
avatar
0

42=-2m-12+6

42+12-6=-2m

48=-2m

48/-2=m

-24=m

Guest Nov 20, 2014
 #3
avatar
0

42=-2(m+6)+6

42=(-2m+-36)+6

42=(-2m=36)+6

42=m=18+6

42=m=24

42=24

ans= 2

Guest Jun 23, 2015
 #4
avatar+7023 
0

42 = -2(m+6)+6

42 = -2m - 12 + 6

42 = -2m - 6

-2m = 48

m = -24

Same as Guest #2's answer.

MaxWong  Jul 27, 2016

9 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.